منهج الادريسي من خلال كتابه - وشاح, غسان (جامعة الوادي - University of Eloued, 2021)
ملخص تناول هذا البحث عدد من النقاط الرئيسة مثل التعريف بالإدريس وتعريف بكتابه نزهة المشتاق ومنهج الإدريسي حيث استخدم منهجاً علمياً دقيقاً في اعداد الكتاب مثل الرجوع للمصادر والمشاهدة والمباشرة والسماع من الأخرين وتناول تقسيمات الإدريسي للعالم لعدد من الأقاليم وصفات ومميزات كل إقليم وأهمية خرائط الإدريسي للعلم الحديث. Al-Idrisi is considered one of the greatest scholars of Islam. He excelled in several sciences in which a number of books were prepared, and Al-Idrisi's journey is one of the most important geographical and historical works. The world was divided into seven regions and he described these regions accurately. Scientifically accurate in preparing the book, such as referring to the sources, watching, direct, and hearing from others.
نزهة المشتاق في اختراق الآفاق
مقال
Keywords: نزهة المشتاق- الإدريسي – روجار- الأقاليم; Nuzhat Al-Mushtaq - Al Idrisi - Rogar - Territories